Inquiring minds: theorizing children's interests. Issue 3 (3rd May 2016) - Hedges, Helen; Cooper, Maria
Abstract: Children's interests are a common foundation for early childhood curricula. Yet, little research is available about the fundamental nature of children's interests and analytical ways to recognize and engage with these. Early work on children's interests adopted a psychological perspective and associated interests with activity choices. Recent work has taken a sociocultural perspective, arguing that more analytical interpretations of children's interests can occur through a deeper understanding of children's funds of knowledge from their lives in their families and communities, and their inquiries that result. This paper draws on a qualitative, interpretivist study in two early childhood centres in Aotearoa New Zealand to extend this work and argue that children's 'real questions' are the fundamental source of their interests. The interpretations presented of children's questions also challenge earlier psychological research that suggested children cannot imagine their future selves until late in the early childhood period. A revised continuum of children's interests and examples of interpretations of children's real questions are proffered for further consideration in other early childhood contexts. Further, the paper argues that interests-based curriculum is justifiable in the early years through likely leading to a range of long-term outcomes valued by societies.